2020
DOI: 10.1002/app.49409
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and cytotoxicity of PCL–PEG–PCL diacrylate and agarose interpenetrating network hydrogels for cartilage tissue engineering

Abstract: Hydrogels are suitable biomaterials for cartilage tissue engineering due to the excellent ability to retain water to provide suitable environment for the tissue, however, the insufficient mechanical properties often prevent their wider applications. The objective of this study was to fabricate biocompatible hydrogels with good mechanical performance, high‐water content, and porous microstructure for cartilage regeneration. Photocrosslinked hydrogels are one of the most widely used systems in tissue engineering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…IPN hydrogels may be preferred over polymer blends due to their improved mechanical strength, controlled swelling behavior and efficient drug loading capacity [ 259 , 261 ]. One of the most used biopolymers for IPN formation is CTS, as reported by Dragan et al (2020) [ 262 ], although there have been a large number of research papers based on IPN hydrogels synthesized with different synthetic and natural polymers, such as COL [ 263 , 264 , 265 ], GEL [ 266 , 267 , 268 ], alginate [ 267 , 269 , 270 ], polyurethane [ 264 , 265 , 270 ], PVA [ 268 , 271 ], PEG [ 272 , 273 ] and poly (aspartic acid) [ 274 ], among other candidate polymers. In this sense, there is a wide range of possibilities by means of materials and synthesis procedures that can be used for IPNs formation, owing to their outstanding physicochemical properties.…”
Section: Hybrid Hydrogel Compositesmentioning
confidence: 99%
“…IPN hydrogels may be preferred over polymer blends due to their improved mechanical strength, controlled swelling behavior and efficient drug loading capacity [ 259 , 261 ]. One of the most used biopolymers for IPN formation is CTS, as reported by Dragan et al (2020) [ 262 ], although there have been a large number of research papers based on IPN hydrogels synthesized with different synthetic and natural polymers, such as COL [ 263 , 264 , 265 ], GEL [ 266 , 267 , 268 ], alginate [ 267 , 269 , 270 ], polyurethane [ 264 , 265 , 270 ], PVA [ 268 , 271 ], PEG [ 272 , 273 ] and poly (aspartic acid) [ 274 ], among other candidate polymers. In this sense, there is a wide range of possibilities by means of materials and synthesis procedures that can be used for IPNs formation, owing to their outstanding physicochemical properties.…”
Section: Hybrid Hydrogel Compositesmentioning
confidence: 99%
“…A summary of compressive mechanical properties of previously reported hydrogels containing more than 60% of water [ 62–75 ] …”
Section: Resultsmentioning
confidence: 99%
“…In addition, when PMAA content in hydrogel was lower, there was not enough PMAA to form strong primary network and efficiently hold gelatin, resulting in a weaker and softer structure. As PMAA content increased, the cross-linking was more efficient and gelatin was firmly embedded in F I G U R E 4 A summary of compressive mechanical properties of previously reported hydrogels containing more than 60% of water [62][63][64][65][66][67][68][69][70][71][72][73][74][75] the network of PMAA. The sharp increase in mechanical performances evidenced within the MAA concentration range from 0.2 to 0.4 ml/ml indicates the formation of strong, interconnected primary network of PMAA.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Additionally, the strong absorption capacity helps maintain cell morphology and pore elastic structure. [ 122 ] Thus, agarose is an ideal sacrificial biomaterial for encapsulating cells. An in‐depth study found that the structure of agarose makes it more stable and harder than that of gelatin.…”
Section: Advances Of Biomaterialsmentioning
confidence: 99%